Structural insights into ribosomal rescue by Dom34 and Hbs1 at near-atomic resolution - Tarek Hilal (Nature Portfolio, 2016)
mRNA surveillance is essential to maintain homeostasis in eukaryotes and is activated by mRNAs lacking a stop codon. Here the authors describe a high resolution cryo-EM structure of a nonstop complex that shows how arrested ribosome recognition is achieved during Dom34-mediated mRNA surveillance.